From the US department of state, USAID, and Washington-based think tanks: The search for ungoverned spaces in South America - Mateo, Luiza R.; dos Santos, Aline P. (Springer Nature, 2014)
The theme of ungoverned areas is connected to that of the so-called new threats, which, as defined by the late 1980s, cover such diverse subjects as terrorism, drug trafficking, illegal migration, organized crime, and handling of weapons of mass destruction (WMD) or of nuclear arsenals. Similarly, this approach touches upon discussions on failed states, weak states, and effective governance. The purpose of this chapter is to understand the nature of the zones of low governability once they have taken on relevance in discussions of international security and have had particular impact on the foreign policy of the United States.